Levodopa therapy in Parkinson's disease: influence on liquid chromatographic tandem mass spectrometric-based measurements of plasma and urinary normetanephrine, metanephrine and methoxytyramine. (January 2014) - Eisenhofer, Graeme; Brown, Sebastian; Peitzsch, Mirko; Pelzel, Daniela; Lattke, Peter; Glöckner, Stephan; Stell, Anthony; Prejbisz, Aleksander; Fassnacht, Martin; Beuschlein, Felix; Januszewicz, Andrzej; Siegert, Gabriele; et al.
Background: Medication-related interferences with measurements of catecholamines and their metabolites represent important causes of false-positive results during diagnosis of phaeochromocytomas and paragangliomas (PPGLs). Such interferences are less troublesome with measurements by liquid chromatography with tandem mass-spectrometry (LC-MS/MS) than by other methods, but can still present problems for some drugs. Levodopa, the precursor for dopamine used in the treatment of Parkinson's disease, represents one potentially interfering medication. Methods: Plasma and urine samples, obtained from 20 Parkinsonian patients receiving levodopa, were analysed for concentrations of catecholamines and their O-methylated metabolites by LC-MS/MS. Results were compared with those from a group of 120 age-matched subjects and 18 patients with PPGLs. Results: Plasma and urinary free and deconjugated (free + conjugated) methoxytyramine, as well as urinary dopamine, showed 22- to 148-fold higher ( P  < 0.0001) concentrations in patients receiving levodopa than in the reference group. In contrast, plasma normetanephrine, urinary noradrenaline and urinary free and deconjugated normetanephrine concentrations were unaffected. Plasma free metanephrine, urinary adrenaline and urinary free and deconjugated metanephrine all showed higher ( P  < 0.05) concentrations in Parkinsonian patients than the reference group, but this was only a problem for adrenaline. Similar to normetanephrine, plasma and urinary metanephrine remained below the 97.5 percentiles of the reference group in almost all Parkinsonian patients. Conclusions: These data establish that although levodopa treatment confounds identification of PPGLs that produce dopamine, the therapy is not a problem for use of LC-MS/MS measurements of plasma and urinary normetanephrine and metanephrine to diagnose more commonly encountered PPGLs that produce noradrenaline or adrenaline.